Muktinath, Nepal: Spiritual Magnetism and Complexity in Space - Poudel, P. C. (Himalayan Review, 2011)
Available with fulltext. Key words: Spiritual magnetism; Pilgrims; Shaligram; Super natural; Sacred geography; Power of place The Himalayan Review Nepal Geographical Society Vol. XXXI 2000 Page: 37-59 Uploaded date: 5 June, 2011